ANALISA TINGKAT PELAYANAN SIMPANG TAK BERSINYAL TIPE T DENGAN METODE HCM 2000 ( Studi Kasus jalan Merdeka Barat Kota Lhokseumawe ) - Hanafiah Hanafiah (Portal: Jurnal Teknik Sipil, 2010)
Lhokseumawe city is the capital of Lhokseumawe City Government as well as the center of trade activities, education and social and culture which every day passed throught by the traffic flow from the surrounding areas. As a result of several potential intersections would be conflict and prone jammed. One of the conflict-prone locations is at the intersection of Jalan Merdeka Barat -Jaya Sakti. This conflict cousted by no traffic signs provided there geometric condition of intersection is not standard, so that during the rush hours tends to be congestion. In connection to these problems, this study tried to analyze performance of the intersection as traffic management solutions to overcome bottlenecks in the area of Jalan Merdeka Barat intersection. Survey data acquisition in the third crossing arm were done by recording the movement of traffic with a handy cam records for 3 days, during rush hours in the morning, afternoon and evening. The results of the analysis method on the condition of existing HCM 2000, the amount of delay on the Eastern arm 19.75 ses/smp, located at the level of service C, the delay arm west and south 30.76 sec/smp, located at the level peleyanan D. Alternative approach road widening the Jalan Jaya Jaya Sakti to 7 meters and Jalan Merdeka Barat to 14 meters, 4-lane 2-way use can reduce the median performace of intersection.Keywords: intersection fermormance, traffic flow, capacity, degree of saturation